Rendemen Giling dan Mutu Beras pada Beberapa Unit Penggiling Padi Kecil Keliling di Kabupaten Banyuwangi - Rosiana Ulfa; Purwiyatno Hariyadi; Tjahja Muhandri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Rice is the staple food for Indonesians. Consequently, rice milling services are in great demand by the rice farmers. The need of rice milling service has increased the number of mobile small scale rice milling units (PPK-keliling), especially at the rice production area. The objective of this research was to determine and compare the yield of milling and quality of the resulted rice due to milling process at mobile small scale rice milling (PPK-keliling) and large milling units (PPB) operating in Banyuwangi Regency. About 12 kg of rice grain each were milled at 12 different PPK units. The resulted white rice (milled and polished rice) were weighted and analyzed for its composition with respect to head rice, broken rice, small broken rice, rice chaffs (rice hulls) and rice brans. The yield and quality of the resulted milled rice were then compared with that of rice resulted from large rice milling units (PPB). There was no signi cant differ- ence in the yield of milling between PPK-keliling (62.40±3.23%) and PPB (64.54±1.21%). However, rice quality resulted from PPK-keliling (containing 28.87±8.76% and 26.34±9.28% of broken rice and small broken rice, respectively) was signi cantly lower than that from PPB (13.50±3.04% and 11.83±6.45% of broken rice and small broken rice, respectively. Overall, even though there was no signi cant different in term of yield between PPB and PPK-keliling, rice resulted from PPK-keliling has lower quality as com- pared with those of PPB.